Parasitoid and Parasitization of Plutella xylostella (L.) (Lepidoptera: Yponomeutidae) in South Sumatera - SITI HERLINDA (HAYATI Journal of Biosciences, 2005)
Surveys from May 2003 to January 2004 in South Sumatera were conducted to determine parasitoid attacking Plutella xylostella (L.) and to estimate P. xylostella parasitization by the parasitoids. The eggs and the larvae of P. xylostella were collected from brassicaceous crops, i.e. mustard, Indian mustard, and cabbage. Six parasitoids found were Trichogrammatoidea cojuangcoi Nagaraja (Hymenoptera: Trichogrammatidae), Cotesia plutellae (Kurdj.) (Hymenoptera: Braconidae), Diadegma semiclausum Hellen (Hymenoptera: Ichneumonidae), Oomyzus sokolowskii (Kurdj.) (Hymenoptera: Eulophidae), Tetrastichus (Hymenoptera: Eulophidae), and a ceraphronid wasp (unidentified species). Trichogrammatoidea cojuangcoi parasitized P. xylostella eggs, however, the others parasitized the larvae except the ceraphronid wasp. In South Sumatera, the ceraphronid wasp was reported for the first time parasitizing D. semiclausum pupae, and its parasitization reached 6.2%. Oomyzus sokolowskii and Tetrastichus were found in this area for the first time, as well. In the highland, D. semiclausum was the most abundant compared to the others where its parasitization reached 79.2%. In the lowland P. xylostella larvae was mainly attacked by C. plutellae with the parasitization reaching 64.9%. In the dry and rainy seasons, the parasitization was mainly exerted by T. cojuangcoi (77.0%) and D. semiclausum (79.2%).